2018
DOI: 10.21037/tau.2018.08.28
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lymph node status in patients with urothelial carcinoma—still in search of the perfect imaging modality: a systematic review

Abstract: While accurate lymph node status evaluation in urothelial carcinoma patients is essential for the correct disease staging and, hence, establishing the most beneficial treatment strategy, the diagnostic performance of routine imaging in regards to this issue is not satisfactory. For the purpose of this article, we systematically reviewed the contemporary literature on the sensitivity and specificity of particular imaging modalities which have been studied for detecting lymph node metastases in patients diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 94 publications
0
4
0
1
Order By: Relevance
“…At present, the use of cutting-edge DL technology to predict the preoperative LNM status of tumors, including gastric cancer (26,27), breast cancer (28), colorectal cancer (29), lung cancer (30), urothelial cancer (31) and EC (7,32), usually relies on the readily-available MRI/ CT and ultrasound imaging. Clinical experience has illustrated that the existing LNM risk stratification criteria, including the Mayo criteria and NCCN guidelines, will expose 75% of EC patients to unnecessary lymphadenectomy (33) and about 10% of low-risk and 15% of early-stage ECs will progress to LNM (34).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the use of cutting-edge DL technology to predict the preoperative LNM status of tumors, including gastric cancer (26,27), breast cancer (28), colorectal cancer (29), lung cancer (30), urothelial cancer (31) and EC (7,32), usually relies on the readily-available MRI/ CT and ultrasound imaging. Clinical experience has illustrated that the existing LNM risk stratification criteria, including the Mayo criteria and NCCN guidelines, will expose 75% of EC patients to unnecessary lymphadenectomy (33) and about 10% of low-risk and 15% of early-stage ECs will progress to LNM (34).…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на то что наиболее эффективным методом выявления локорегионарного рецидива/прогрессирования у пациентов с иРМП считается 18 FDG-PET/КТ [5], для диагностики регионарного метастазирования допускается использование как компьютерной, так и магнитно-резонансной томографии. МРТ, в частности, позволяет диагностировать регионарное лимфогенное метастазирование в 76% случаев [14]. Наше наблюдение также подтверждает высокую эффективность использования МРТ для диагностики УР после ЦЭ.…”
Section: Discussionunclassified
“…Initially, its use was limited in patients with BC due to the high urinary excretion activity of the ureters and bladder ( 7 ). Nevertheless, several studies have shown that PET/CT has a higher sensitivity in the determination of LN and distant metastases than CT and MRI, and it has caused a therapy management alteration in 19-68% of BC patients ( 8 , 9 , 10 ). Therefore, 18 F-FDG PET/CT is increasingly being used in clinical practice, and its exact role continues to be evaluated ( 6 ).…”
Section: Introductionmentioning
confidence: 99%